Resistance of the Subject in Branko Čegec’s Poetry - Jakić, Lucija; Buljubašić Srb, Ivana (Anafora, 2023)
The article analyses cultural and media traces in Branko Čegec’s poetry. They are researched, described, and interpreted from the perspective of subject structure in the three texts from Čegec’s three poetry collections published in the 1980s – “Genesis (domovina): vazda i dovijeka” from Eros-Europa-Arafat, “Abcčćdđdžefghijklmnnjoprsštuvzž” from Zapadno-istočni spol, and “Stanje stvari” from Melankolični ljetopis. The article explores the differences between individual and collective memory (J. Assmann), and the dominant and emergent culture (R. Williams), whereby the text becomes the space in which they clash. Traces of cultures and media are most often observed among the motifs, and their effects are notably in the resistance of subject structures that critically undermine the prevailing discourses of power, primarily through linguistic and discursive games.